Hubungan Lama Menstruasi, Konsumsi Zat Besi dan Status Gizi dengan Kejadian Anemia pada Remaja Putri - Royani Chairiyah (Universitas Muhammadiyah Semarang, 2022)
Background: Anemia in adolescent girls is a condition in which hemoglobin levels in the blood are lower than normal, and normal Hb levels in adolescent girls. Objective: Analyze the long-standing relationship of menstruation, nutritional status, and iron consumption against anemia in adolescent girls. Method: The study involved 64 teenagers in al-Ittihad boarding school with cross sectional design with a type of analytical quantitative research conducted in July 2021. Dependent Variables: in this study anemia in adolescents, Independent Variables of menstrual length, consumption of iron, and nutritional status. Data analysis is done with Univariate and Bivariate analysis with Chi -Square test. Primary data is obtained from an adolescent's hemoglobin examination, while the secondary data comes from questionnaires filled out directly by adolescents in boarding schools. Result: showed that the incidence of adolescent anemia was 22 people (34.4%). Bivariate analysis showed no association between menstrual length and the incidence of anemia (p = 0.224) CI 95%, no association of iron consumption with anemia (p = 0.199) CI 95% and there was a relationship between nutritional status with the frequency of anemia (p = 0.003) 95% CI. Conclusion: Nutritional status is related to the frequency of anemia but menstrual length is not related to the frequency of anemia and iron consumption is not related with the frequency of anemia in adolescent girls